2006
DOI: 10.1093/brain/awl177
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure and haemoglobin A1c are associated with microhaemorrhage in CADASIL: a two-centre cohort study

Abstract: Cerebral autosomal dominant arteriopathy with subcortical infarcts and leucoencephalopathy (CADASIL) is a hereditary arteriopathy caused by mutations of the Notch3 gene. The risk factors for cerebral microhaemorrhages (CM), their relationship to other MRI lesions in the disease and their potential clinical impact have not been previously defined. Our purpose was to examine the frequency, number and location of microhaemorrhages in a multicentre cohort study, defining predisposing factors and associated radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
149
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 180 publications
(166 citation statements)
references
References 55 publications
11
149
0
6
Order By: Relevance
“…The authors suggested that this could have pathogenic implication in the development of cerebral ischemic complications. The development of microbleeds (but not of ischemic lesions or the volume of white matter changes) in CADASIL seems to be correlated with a history of hypertension and the levels of systolic blood pressure (and glicated hemoglobin) 70 . These arguments in favor of reducing BP routinely in CADASIL, however, should be confronted with evidence that these patients have problems in autoregulation of cerebral blood flow (CBF) (see section on pathogenesis).…”
Section: Treatment Of Cadasilmentioning
confidence: 93%
See 1 more Smart Citation
“…The authors suggested that this could have pathogenic implication in the development of cerebral ischemic complications. The development of microbleeds (but not of ischemic lesions or the volume of white matter changes) in CADASIL seems to be correlated with a history of hypertension and the levels of systolic blood pressure (and glicated hemoglobin) 70 . These arguments in favor of reducing BP routinely in CADASIL, however, should be confronted with evidence that these patients have problems in autoregulation of cerebral blood flow (CBF) (see section on pathogenesis).…”
Section: Treatment Of Cadasilmentioning
confidence: 93%
“…Asymptomatic microbleeds (predominantly in the thalamus, basal ganglia and brainstem) are even more common, and seem to increase in incidence with advancing age of the patients [67][68][69] (Fig 2). Predisposing factors for cerebral bleeding are poorly understood but may include, in addition to microhemorrhages, the extent of white matter changes and ischemic lesion burden, the use of antiplatelet agents, disturbances in glucose metabolism and hypertension 68,70 .…”
Section: Lacunar Infarcts and Other Cerebrovascular Injuriesmentioning
confidence: 99%
“…19 The total volume of WMH was normalized to the intracranial compartment (ICC) in each patient (normalized volume of WMH or nWMH 5 [volume of WMH/volume ICC] 3 100) 20 and logarithmically transformed due to its non-normal distribution.…”
mentioning
confidence: 99%
“…We have previously reported a high inter-rater concordance within our group for MB, 21 WMH, 19 and lacunar infarcts. 20 Regarding DPVS, 15 scans randomly chosen were handed to a second rater (E.A.) for evaluation, and intraclass correlation coefficients were calculated.…”
mentioning
confidence: 99%
“…While CADASIL is considered to be a primarily ischemic form of cerebral vascular disorder, microbleeds have recently been reported in 31-69% of symptomatic NOTCH 3 mutation carriers (19,20). Viswanathan et al (21) reported that hypertension and HbA1c are associated with microbleeds in CADASIL. Because Patient 2 did not exhibit either hypertension or DM, ticlopidine might have been associated with his ICH.…”
Section: Discussionmentioning
confidence: 99%